Media community of football fans in Indonesia: Conditions, problems, and challenges - Junaedi, Fajar; Muhammad, Helmy (Jurnal Komunikasi, 2026)
This study examines the conditions, challenges, and problems faced by such media in 2022 -2025. Five community media are the focus of this research, namely Ongisnade, Simamaung, Football Fandom, Sleman Football, and Emosi Jiwaku. Data were collected usingsemi-structured interviews with key personnel from each media outlet and through systematic analysis of relevant documents produced by these communities. The results showed that the development of football community media in Indonesia occurred during the digital media era. The ease of producing and distributing media has encouraged the establishment of a football community media, at the same time, showcasing the rise of well-informed football fans. Football fans' ability to manage the media within the football community demonstrates that they in Indonesia have transformed, becoming well-educated and informed. This study also identified the challenges faced by the football community media, including securing funding to ensure sustainability, managing and filling content with human resources, and the critical attitude shown in reporting on clubs, which can trigger bad relations with club management.